New agroforestry techniques - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
An agroforestry technique using Faidherbia albida, more commonly known as Acacia albida, has now been perfected and can be easily applied by farmers who are aware of the potential of this tree. Seeds harvested between January and April are hulled,...